2018
DOI: 10.1055/s-0038-1668541
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Difference in Hospital Stay between Patients undergoing Translabyrinthine or Retrosigmoid Surgery for Vestibular Schwannoma Stratified by Tumor Size?

Abstract: Objective To date, no European study has compared approach-specific outcome data in vestibular schwannoma (VS) surgery stratified by tumor size. We analyzed hospital length of stay (LOS), intensive therapy/high-dependency unit (ITU/HDU) LOS, and complications in patients undergoing VS surgery via the translabyrinthine (TL) versus retrosigmoid (RS) approaches, stratifying for tumor size. Design Prospective database undergoing retrospective review. Setting Tertiary center. Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Previous studies have shown that tumor size is correlated with postoperative LOS following VS surgery. 27,35 However, to our knowledge this is the first study to specifically look at brainstem compression as an independent predictor of LOS regardless of tumor size. Larger tumors are more often associated with brainstem compression, which can complicate surgery and postoperative care, thereby increasing LOS.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Previous studies have shown that tumor size is correlated with postoperative LOS following VS surgery. 27,35 However, to our knowledge this is the first study to specifically look at brainstem compression as an independent predictor of LOS regardless of tumor size. Larger tumors are more often associated with brainstem compression, which can complicate surgery and postoperative care, thereby increasing LOS.…”
Section: Discussionmentioning
confidence: 93%
“…26 Beyond the economic implications of LOS, prolonged hospital stay may place an otherwise healthy patient at risk of nosocomial infections. 27 Previous reports in the general surgery literature demonstrate advanced age impacts postoperative LOS. 28,29 Additionally, previous data has shown advanced age significantly impacts intensive care LOS following VS surgery, 25 and advanced age (>65 years) prolongs hospital LOS following VS surgery.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…As with any observational study, there is inevitably unmeasured confounding that may account for some of the observed association between excess time in the hospital and facility volume. Surgical approach, for example, is associated with length of stay independent of tumor size . Surgeon volume may play a role in perioperative complications and prolonged length of stay, but surgeon-level data are not available in the NCDB.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical approach, for example, is associated with length of stay independent of tumor size. 26 Surgeon volume may play a role in perioperative complications and prolonged length of stay, but surgeon-level data are not available in the NCDB. Variance in length of stay may also be associated with the day of the week surgery is performed, as surgeries performed later in the week must contend with more limited staffing on the weekends, which may be associated with prolonged stay.…”
Section: Strengths and Limitationsmentioning
confidence: 99%